SYNTAX: EXPLORING MINOR AND MAJOR CATEGORIES WITH A FOCUS ON PHRASES AND SENTENCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the fundamental aspects of syntax in language, dividing it into two main categories: minor syntax and major syntax, and focusing on their respective roles and features. Minor syntax includes short, context-dependent expressions like greetings and exclamations, which are often informal yet essential for communication. Major syntax, in contrast, deals with the construction of fully developed sentences and clauses, facilitating the expression of complex ideas. The article further examines the two core components of syntax: phrases and sentences. Phrases function as building blocks within sentences, while sentences themselves represent complete thoughts. By distinguishing these elements, the discussion highlights how syntax organizes language into meaningful structures. The conclusions emphasize the interplay between minor and major syntax, as well as the practical significance of understanding these systems. This dual approach—balancing simplicity and complexity—enhances both our theoretical grasp of language and its practical use in communication. The article underscores syntax as a vital component of linguistic expression, combining clarity with the flexibility necessary for human interaction.